A comparison of the efficiency of human embryo intestine, Hep 2 cells, and human embryo kidney cells for the primary isolation of ophthalmic viruses. Issue 8 (August 1981) - Cubitt, W. D.; McSwiggan, D. A.; Thaker, U.; Darougar, S.
Abstract : A comparison has been made of the efficiency of 3 cell systems, human embryo kidney (HEK), Hep 2, and a continuous line of human embryo intestine (HEI), for the isolation of ophthalmic viruses. A total of 40 herpes simplex, 51 adenoviruses, and 2 vaccinia viruses were isolated from 323 specimens. HEK cells were found to be the optimal system, 85 out of 93 (91%) of the viruses being detected in these cells alone. However, HEK cells are difficult to obtain, and therefore the use of a combination of the continuous cell lines HEI and Hep 2 is recommended as an alternative. 89% of the viruses were detected by this combination. The use of either HEI or Hep 2 cells alone was unsatisfactory.